2017
DOI: 10.7759/cureus.1682
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Ganglion Cyst and Mucoid Degeneration: A Review

Abstract: Mucoid degeneration and ganglion cyst are two distinct non-traumatic lesions of the anterior cruciate ligament (ACL) that most commonly occur discretely but occasionally coexist. They are relatively uncommon, and their exact aetiopathogenesis is still not clear. ACL ganglion cyst occurs more frequently among relatively younger patients compared to mucoid degeneration. They could be asymptomatic and discovered incidentally while evaluating the knee for other pathologies. Symptomatic cases of the two conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“… 1 2 4 5 7 9 10 11 12 13 14 15 16 17 19 20) As noted in previous reports, clinical symptoms of MD of the ACL include nonspecific knee pain with limitation of the range movement and ligament stability. 7 9 18 19 20) None of our patients knew precisely when their symptoms started, but all had persistent knee pain in terminal flexion for at least 12 months, which was distinct from acute extension pain caused by meniscus bucket-handle tears. The fact that our patients did not have a trauma prior to the onset of knee pain and their symptoms did not respond to nonsteroidal anti-inflammatory drugs and physiotherapy helped us to suspect MD of the ACL.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“… 1 2 4 5 7 9 10 11 12 13 14 15 16 17 19 20) As noted in previous reports, clinical symptoms of MD of the ACL include nonspecific knee pain with limitation of the range movement and ligament stability. 7 9 18 19 20) None of our patients knew precisely when their symptoms started, but all had persistent knee pain in terminal flexion for at least 12 months, which was distinct from acute extension pain caused by meniscus bucket-handle tears. The fact that our patients did not have a trauma prior to the onset of knee pain and their symptoms did not respond to nonsteroidal anti-inflammatory drugs and physiotherapy helped us to suspect MD of the ACL.…”
Section: Discussionmentioning
confidence: 90%
“…Both lesions of ACL are two different entities that occasionally coexist. 18) The aim of this study was to detail the clinical, radiological, arthroscopic and pathological findings of this condition and report the clinical outcomes following arthroscopic treatment of MD of the ACL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDACL was subject of many clinical cases and short heterogeneous series [1][2][3][7][8][9][10][11][12][13][14][15][16][17][18]. All previous studies confirmed that clinical symptoms of MDACL include mostly posterior knee pain with limitation of the range movement and sometimes deteriorated ligament stability [10,11,[17][18][19]. Moreover, most patients did not have a trauma prior to the onset of knee pain and their symptoms did not respond to nonsteroidal anti-inflammatory drugs and physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these ganglion cysts were found incidentally without symptoms and often coexisted with MD-ACL. Although the pathogenesis of ACL ganglion cysts remains controversial [ 23 , 25 , 26 ], in our opinion, there are similarities to those of MD-ACL, including trauma theories. Krudwig et al [ 9 ] reported that symptoms, such as pain and limited ROM, were found in only 11% of their cases, and that these symptoms were related to the size and location of the ganglion cysts [ 25 ].…”
Section: Discussionmentioning
confidence: 99%